Productive economic development of the Curahuasi district - Abancay province - Apurímac Region - Paredes Quiroz, Luis Ricardo (2023)
The objective of the research was to establish the degree of influence of the productive linkages and productive systems in the productive economic growth of the Curahuasi district, Abancay province - Apurímac region - period 2010-2015. Work was done with 22 territorial actors between associations and individual producers. The technique of documentary collection and survey was used. The results showed that the agriculture, livestock, hunting and forestry sector represents 30% of GDP; the gross domestic product increased to 37.1%; 81.6% are individual farmers, 90.9% are dedicated to the economic activity of the agricultural sector, the productive linkages, show 81.8% of the suppliers are from Curahuasi, 54.5% of services are located in Abancay. In production systems, 63.6% of sales occur in the local market, 54.5% are direct sales, and 72.7% use own brands. 72.8% consider that the location of competitors is of little or regular importance; and for 81.8% microenterprises are the most important competitors; price being the most competitive factor. The degree of influence of the productive linkages and productive systems in the productive economic development, has been significant in the economic well-being, meanwhile, in the social well-being, no improvement is appreciated.